2018
DOI: 10.1007/s00405-018-5058-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of cyclooxygenase-2 and cyclin D1 in salivary gland tumors

Abstract: The overexpression of COX-2, observed only in MEC, emphasizes that salivary gland tumors have different profiles. Cyclin D1 is more immunoexpressed in malignant tumors. Together, these immunohistochemical findings may be useful in differentiating the studied tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“… 15 , 30 Furthermore, this prominent diffuse distribution in pleomorphic adenoma demonstrates the role of cyclin D1 in the rapidly expanding growth of even benign-looking tumors. High mixed nuclear and cytoplasmic intracellular localization was seen in pleomorphic adenoma, similar to the study of Tenorio et al 14 …”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“… 15 , 30 Furthermore, this prominent diffuse distribution in pleomorphic adenoma demonstrates the role of cyclin D1 in the rapidly expanding growth of even benign-looking tumors. High mixed nuclear and cytoplasmic intracellular localization was seen in pleomorphic adenoma, similar to the study of Tenorio et al 14 …”
Section: Discussionsupporting
confidence: 88%
“…All studied benign salivary tumors expressed cyclin D1 (100%), frequently showed diffuse scoring and were most commonly detected in pleomorphic adenoma. Another study by Tenorio et al 14 revealed only 60.5% positivity with mild scoring of pleomorphic adenoma. On the other hand, Jour et al 15 study displayed cyclin D1 expression in 93% of benign tumors, with predominant moderate scoring in both pleomorphic adenoma and warthin tumors.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, Sakurai et al found that the expression of COX-2 was group-dependent and increased from the normal salivary glands, to the salivary gland adenomas, with the highest expression detected in the salivary gland carcinoma group [31]. Furthermore, two studies found that the level of COX-2 in mucoepidermoid carcinoma (MEC) was strongly increased, whereas most of the pleomorphic adenomas and adenoid cystic carcinomas (AdCC) were COX-2-negative [46,47]. In melanomas, Nascimento et al found that oral melanomas were consistently COX-2-positive compared with the benign oral nevi, which were completely COX-2-negative [48].…”
Section: Cox-2 Expression In Other Head and Neck Tumorsmentioning
confidence: 99%
“…Our previous study has demonstrated that the expression of cyclin D1 was upregulated in AdCC when compared with PMA and/or NSG (Bu et al., 2015). In addition, the expression of cyclin D1 is upregulated in MEC and plays an important role in the Wnt‐signaling pathway to produce poor prognosis and poorly differentiated tumor staging of MEC (Shiratsuchi et al., 2007; Tenorio et al, 2018). In this study, we found that SIX1 and AP2M1 were correlated with cyclin D1, so we can propose a hypothesis that SIX1 and AP2M1 play an important role in AdCC and MEC proliferation similar to that of cyclin D1.…”
Section: Discussionmentioning
confidence: 99%